Vibration signal correction of unbalanced rotor due to angular speed fluctuation. (July 2018) - Cao, Hongrui; He, Dong; Xi, Songtao; Chen, Xuefeng
Highlights: The effect of angular speed fluctuation on vibration signal is analyzed quantitatively. A novel vibration signal correction method is proposed for unbalanced rotor. The proposed method is verified with both simulations and experiments. Abstract: The rotating speed of a rotor is hardly constant in practice due to angular speed fluctuation, which affects the balancing accuracy of the rotor. In this paper, the effect of angular speed fluctuation on vibration responses of the unbalanced rotor is analyzed quantitatively. Then, a vibration signal correction method based on zoom synchrosqueezing transform (ZST) and tacholess order tracking is proposed. The instantaneous angular speed (IAS) of the rotor is extracted by the ZST firstly and then used to calculate the instantaneous phase. The vibration signal is further resampled in angular domain to reduce the effect of angular speed fluctuation. The signal obtained in angular domain is transformed into order domain using discrete Fourier transform (DFT) to estimate the amplitude and phase of the vibration signal. Simulated and experimental results show that the proposed method can successfully correct the amplitude and phase of the vibration signal due to angular speed fluctuation.